Synthetic Peptide Libraries Designed From a Minimal Alpha-Helical Domain of AS-48-Bacteriocin Homologs Exhibit Potent Antibacterial Activity - Ross, Jessica N.; Fields, Francisco R.; Kalwajtys, Veronica R.; Gonzalez, Alejandro J.; O’Connor, Samantha; Zhang, Angela; Moran, Thomas E.; Hammers, Daniel E.; Carothers, Katelyn E.; Lee, Shaun W. (Frontiers in Microbiology, 2020)
The ribosomally produced, circularized bacteriocin enterocin AS-48 produced by Enterococcus sp. exhibits antibacterial activity through membrane disruption. The membrane penetrating activity of enterocin AS-48 has been attributed to a specific alpha-helical region on the circular peptide. Truncated, linearized forms containing these domains have been shown to preserve limited bactericidal activity. We utilized the amino acid sequence of the active helical domain of enterocin AS-48 to perform a homology-based search of similar sequences in other bacterial genomes. We identified three previously uncharacterized AS-48-like bacteriocin genes in Clostridium sordellii, Paenibacillus larvae, and Bacillus xiamenensis. Enterocin AS-48 and homologues from these bacterial species were used as scaffolds for the design of a minimal peptide library based on the active helical domain of each bacteriocin sequence. 95 synthetic peptide variants of each scaffold peptide, designated Syn-enterocin, Syn-sordellicin, Synlarvacin, and Syn-xiamensin, were designed and synthesized from each scaffold sequence based on defined biophysical parameters. A total of 384 total peptides were assessed for antibacterial activity against Gram-negative and Gram-positive bacteria. Minimal Inhibitory Concentrations (MICs) as low as 15.6 nM could be observed for the most potent peptide candidate tested, with no significant cytotoxicity to eukaryotic cells. Our work demonstrates for the first time a general workflow of using minimal domains of natural bacteriocin sequences as scaffolds to design and rapidly synthesize a library of bacteriocin-based antimicrobial peptide variants for evaluation.